Plan de implementación de un sistema de gestión de seguridad y salud en el trabajo basado en la norma NTC ISO 45001:2018 para una pyme fabricante de productos de limpieza y desinfección (2019)
The purpose of this monograph is to develop a proposed plan for the implementation of the Occupational Health and Safety System under the requirements of the NTC ISO 45001: 2018 standard; in a company dedicated to the manufacture of disinfection and cleaning products, located in the city of Bogotá. The work of degree, incorporates the general diagnosis of the current situation of the company against the requirements of the standard; where the main deficiencies or compliance gaps were identified and possible evidences that will fulfill said requirements were proposed.